PKM DEVELOPMENT OF BUSINESS OPPORTUNITIES FOR COFFEE FARMERS IN WARNASARI VILLAGE, SUBDISTRICT PANGALENGAN, DISRICT BANDUNG - Dhini Ardianti; Ida Hindarsah; Taufik Hidayatullah; Vera Hermawan (LPM Universitas Pasundan, 2020)
Pangalengan is one of the districts in Bandung Regency which is an agricultural center. One of the potential products in the Pangalengan area is Pangalengan coffee which is well known to foreign countries. However, not all of the village areas in Pangalengan coffee farming have not been made a top priority, so there is still a need for coaching and mentoring as the PPM team of this group is serving together with the PPM team of the Faculty of Social and Political Sciences (FISIP) Unpas in February 2019 in Warnasari Village, Pangalengan District Bandung. The problems identified in the partners are human resources, raw materials, production, products, and marketing. The target or partners in this activity are coffee farmers in the Warnasari Village, Pangalengan. The method of activities includes social mapping related to the identification of problems faced by coffee farmers and FGDs with entrepreneurship material. The results of this period PPM devotion shows a change in the mindset of coffee farmers to turn coffee into a priority or mainstay of the region's commodities, in addition to the awareness related to the increasing spirit of entrepreneurship desiring to process coffee yields with variant forms in the future. The next target is the need for further service programs from the social mapping and FGD results from this period. in addition there is also an awareness related to the increasing spirit of entrepreneurship in wanting to process coffee yields with variant forms in the future. The next target is the need for further service programs from the social mapping and FGD results from this period. in addition there is also an awareness related to the increasing spirit of entrepreneurship in wanting to process coffee yields with variant forms in the future. The next target is the need for further service programs from the social mapping and FGD results from this period.